NaCl salinity and Zn foliar application influence essential oil composition of basil (Ocimum basilicum L.) - Mohammad Bagher HASSANPOURAGHDAM; Gholam Reza GOHARI; Seied Jalal TABATABAEI; Mohammad Reza DADPOUR; Mehdi SHIRDEL (Acta Agriculturae Slovenica, 2011)
Essential oils composition of hydroponically grown Ocimum basilicum L. plant was evaluated in response to salinity (control and 50 mM NaCl) and Zn foliar application (control, 100 and 200 mg l-1). Essential oil constituents were quantified and identified by GC/EI-MS. In total, fifty seven components were identified in the six treatment combinations. Methyl chavicol (43.9–61.2 %) and linalool (11.4-16%) were the major components of all treatments. Salinity had deteriorative effect on methyl chavicol biosynthesis and accumulation. In contrast, integrated levels of salinity and 200 mgl-1 Zn had increment effects on linalool content. Germacrene D (2.2-3.9 %), 1,8-cineole (2.4-3.8 %), (Z)-α-bergamotene (0.1-2.6 %), (E)-β-farnesene (1.4-2.6 %), α-bulnesene (0.9-2.4 %), camphor (0.7-1.3 %) and  (E)-β-ocimene (0.2-1.3 %) were the other main common constituents of oil. Considering the constant levels of zinc foliar application, salinity had raising effects on the contents of most above mentioned constituents. In conclusion, it seems that moderate salinity stress along with balanced levels of Zn foliar application changed the primary metabolites pathways in favor of major volatile oil components biosynthesis and that basil plant has the production potential under prevalent semi-saline conditions.